Patterns of Profit Sharing in Professional Firms - Morris, T; Pinnington, A (1998)
Examines the extent to which new forms of profit-sharing based on individual performance have been introduced in professional firms. Data on large law firms; Results showing that profit-sharing are limited in scope; Possible link with the more systematic control of the core of professional staff and more business-like methods of managing; Factors driving profit-sharing policies.